PENGUMUMAN LABA, KEPEMILIKAN MANAJERIAL, DAN REAKSI PASAR - , Yensawai Enggelina Rumbiak, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Investors in capital market using many instruments for making an investment at one or more company. Stock is one of instruments that investor using for an investment. Stock price is influenced by internal company factors, one of them is earning. This show that annual earnings announcement in stock exchange are one of important factors for investors. The annual earnings announcements might release good news or bad news. Good news indicate earnings are higher than the expectation, while bad news indicate or over than expectation. Some previous empirical studied show that earning increase (decrease) are respondent by positive (negative) reaction. As an addition, the study also examines moderating effect of information asymmetry in earning announcement to market reaction. Managerial ownership is the proxy of information asymmetric. Using three models of increasing and decreasing earnings, the analysis show that increasing earning created positive market reaction and decreasing earning created negative market reaction. Others hypothesis that examined managerial ownership show that the ownership weakens market reaction for increasing and decreasing earnings. This is caused by the fact that companies with managerial ownership have better quality of information than that at non managerial ownership companies.